2008
DOI: 10.4049/jimmunol.180.2.988
|View full text |Cite
|
Sign up to set email alerts
|

Protein Interactions between CD2 and Lck Are Required for the Lipid Raft Distribution of CD2

Abstract: In T lymphocytes, lipid rafts are preferred sites for signal transduction initiation and amplification. Many cell membrane receptors, such as the TCR, coreceptors, and accessory molecules associate within these microdomains upon cell activation. However, it is still unclear in most cases whether these receptors interact with rafts through lipid-based amino acid modifications or whether raft insertion is driven by protein-protein interactions. In murine T cells, a significant fraction of CD2 associates with mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 58 publications
(61 reference statements)
1
6
0
Order By: Relevance
“…TCR engagement is followed by the formation of an immunological synapse, where TCR-associated molecules and selected cytosolic signaling effectors are clustered to allow for more efficient signal transduction and amplification . The formation of immunological synapse requires repositioning of membrane lipid rafts, during which CD2 exhibits inducible translocation to lipid rafts and becomes integral to the structure of the immunological synapse. , Notably, CD2 translocation to the immunological synapse of TCR leads to physical association with Lck, supporting our findings. An affinity purification proteomic study of Lck similarly identified CD2 as an Lck interactor in primary mouse CD4+ T cells .…”
Section: Resultssupporting
confidence: 85%
“…TCR engagement is followed by the formation of an immunological synapse, where TCR-associated molecules and selected cytosolic signaling effectors are clustered to allow for more efficient signal transduction and amplification . The formation of immunological synapse requires repositioning of membrane lipid rafts, during which CD2 exhibits inducible translocation to lipid rafts and becomes integral to the structure of the immunological synapse. , Notably, CD2 translocation to the immunological synapse of TCR leads to physical association with Lck, supporting our findings. An affinity purification proteomic study of Lck similarly identified CD2 as an Lck interactor in primary mouse CD4+ T cells .…”
Section: Resultssupporting
confidence: 85%
“…SHP‐1, or modulating the activity of signaling‐enhancing tyrosine kinases 28, 29. Alternatively, given that CD6 associates with several kinases, it might sequester these kinases away from the TCR apparatus or it could function analogously to the IgSF glycoprotein CD2, which transduces mitogenic signals via its association with lipid rafts and the tyrosine kinases Lck and Fyn 30, 31, and inhibitory signals via its association with CD5 32–34. Since CD5 and CD6 also associate at the surface of T cells and one major effect of CD6 stimulation is the phosphorylation of CD5 13, it is feasible that CD5 can integrate or transform the signals generated by the triggering of CD6.…”
Section: Discussionmentioning
confidence: 99%
“…Transient transfections of primary T lymphocytes and of Raji cells were performed as described previously 21. Jurkat E6.1 cells were stably transfected as described previously 31. K562 cells (5×10 6 ) were transfected with 50 μg of hCD166/pECFP‐N2 or rCD166/pECFP‐N2 and by electroporation at 500 μF and 875 V and cultured in complete RPMI supplemented with 5 mg/mL of G418 (Invitrogen) to select for positive cells.…”
Section: Methodsmentioning
confidence: 99%
“…These membrane microdomains are heterogeneous (54) and highly mobile (55), and receptors such as CD5 may serve as scaffolds that allow distinct types of rafts and their components to interact (56). CD5 associates with CD2 and with the TCR (23, 57), and these two surface receptors signal via Src kinases in the context of lipid rafts (33, 58). As we show here that CD5 is present at the cell surface as a homodimer, this may promote further the establishment of interaction arrays with a variety of lipid raft and signaling receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Sucrose gradient centrifugation was performed as described (33). Briefly, activated cells were washed twice with ice-cold PBS and lysed for 30 min on ice in 1 ml of MBS buffer (25 m m MES, pH 6.5, 150 m m NaCl) containing 1% Triton X-100, 1 m m PMSF, and protease inhibitors (1 m m 4-(2-aminoethyl)benzenesulfonyl fluoride, 0.8 μ m aprotinin, 50 μ m bestatin, 15 μ m E-64, 20 μ m leupeptin, 10 μ m pepstatin A; Calbiochem).…”
Section: Methodsmentioning
confidence: 99%